2022
DOI: 10.3389/fimmu.2022.893844
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Allergic Airway Inflammation by Acetylcholine

Abstract: Acetylcholine (ACh) from neuronal and non-neuronal sources plays an important role in the regulation of immune responses and is associated with the development of several disease pathologies. We have previously demonstrated that group 2 innate lymphoid cell (ILC2)-derived ACh is required for optimal type 2 responses to parasitic infection and therefore sought to determine whether this also plays a role in allergic inflammation. RoraCre+ChatLoxP mice (in which ILC2s cannot synthesize ACh) were exposed to an all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…However, active AChE administration at baseline increased IL-5 and IL-13 levels from lung ILC2s, and M2 macrophage numbers. Overall, these results suggest that ACh suppresses airway neutrophilia by reducing CXCL1/CXCL2 levels and may play an in-direct role in negatively regulating ILC2-mediated allergic airway inflammation ( 16 ).…”
Section: Cholinergic Neurotransmitter Signalingmentioning
confidence: 85%
See 1 more Smart Citation
“…However, active AChE administration at baseline increased IL-5 and IL-13 levels from lung ILC2s, and M2 macrophage numbers. Overall, these results suggest that ACh suppresses airway neutrophilia by reducing CXCL1/CXCL2 levels and may play an in-direct role in negatively regulating ILC2-mediated allergic airway inflammation ( 16 ).…”
Section: Cholinergic Neurotransmitter Signalingmentioning
confidence: 85%
“…Importantly, the effects of ChAT deletion are ILC2 specific as the effector and proliferative capacities of lung CD4 + T cells which also produce ACh and express RORɑ ( 15 ) remained unaffected between the two genotypes ( 13 ). Conversely, Rora Cre+ ChAT LoxP mice intranasally challenged with AA extract exhibited more inflammatory M1 macrophages and neutrophil chemo-attractants CXCL1/CXCL2, while maintaining similar eosinophil, ILC2, and type 2 cytokine levels in the BAL fluid ( 16 ). These findings reveal that ChAT induced ACh production in ILC2s is critical for ILC2-mediated parasite clearance and prevention of airway neutrophilia.…”
Section: Cholinergic Neurotransmitter Signalingmentioning
confidence: 99%
“…Lung ILC2s express various subunits of both receptors 126 and can produce ACh in response to A. alternaria challenge or alarmins such as IL-33 and IL-25 126 , 127 . Although neither study examined the cholinergic role of ILC2s in allergic responses, a subsequent study revealed distinct effects of ACh during allergen-induced airway inflammation 128 . While ILC2-derived ACh limits neutrophilic inflammation by reducing the expression of the neutrophil chemoattractants CXCL1 and CXCL2, non-ILC2-derived ACh enhances ILC2-driven type 2 responses and subsequent eosinophilia 128 .…”
Section: The Regulation Of Ilc2 Function In the Lungsmentioning
confidence: 98%
“…Although neither study examined the cholinergic role of ILC2s in allergic responses, a subsequent study revealed distinct effects of ACh during allergen-induced airway inflammation 128 . While ILC2-derived ACh limits neutrophilic inflammation by reducing the expression of the neutrophil chemoattractants CXCL1 and CXCL2, non-ILC2-derived ACh enhances ILC2-driven type 2 responses and subsequent eosinophilia 128 . In contrast, activation of the α7 nicotinic acetylcholine receptor (α7nAChR) by various agonists, such as nicotine and PNU-282987, mitigates ILC2-mediated AHR and airway inflammation in the A. alternaria model 129 , 130 .…”
Section: The Regulation Of Ilc2 Function In the Lungsmentioning
confidence: 98%